Construction of Peace Zones Project: Analysis of the perception of girls and adolescents about violence and peace in the community of Guararí. - López-Céspedes, Sharon (2019)
Building Zones of Peace (BZP) Project: Analysis of the perception of girls and adolescents about violence and peace in the community of Guararí is part of the efforts made by the Universidad Nacional, through the Office of Extension, in carrying out the “Cultural Cities” project, which together with the Municipality of Heredia and the Civic Center for Peace (CCP) of Guararí, articulate processes for the prevention of violence and the construction of peace, focused mainly on children, adolescents and youth at risk.